Experiment and calculation of reinforced concrete at elevated temperatures - Guo, Zhenhai (Butterworth-Heinemann, 2011)
"Comprehensive and readable, this book provides the tools and techniques to properly analyze the effects of high temperature on reinforced concrete, leading to safer, more stable structures. Based on years of the author's research, Reinforced Concrete at Elevated Temperatures' four part treatment starts with an unambiguous and thorough exposition of the mechanical behaviours of materials at elevated temperature, followed by a discussion of temperature field of member sections, mechanical behaviours of members and structures at elevated temperature, and theoretical analysis and practical calculation methods. The book provides unique insight into: - Coupling thermal-mechanical constitutive relation of concrete - Exceptional analyses of beams and columns of rectangular section with three surfaces and two adjacent surfaces exposing to high temperature - Measurement and analysis of redistribution of internal forces of statically indeterminate structure during heating-loading process - Finite element analysis and calculation charts for two-dimensional temperature field of structural members With this book, engineers and architects can effectively analyze the result of high temperature on concrete and materials which will lead to better designs of fire resistant structures, as well as damage evaluation and treatment after fire"-- Provided by publisher.
Machine generated contents note : Introduction Part 1 Mechanical Behavior of Materials at Elevated Temperatures Chapter 1 Strength of Concrete at Elevated Temperatures Chapter 2 Deformation of Concrete at Elevated Temperature Chapter 3 Temperature-Stress Paths and Coupling Constitutive Relation of Concrete Chapter 4 Mechanical Behavior and Constitutive Relation of Reinforcement at Elevated Temperatures Part 2 Temperature Field on Cross-Section of Structural Member Chapter 5 Temperature-Time Curve of Fire and Equation of Heat Conduction Chapter 6 Theoretical Analysis of Temperature Field Chapter 7 Calculation Charts for Temperature Field on Cross-Section Part 3 Mechanical Behavior of Members and Structures at Elevated Temperatures Chapter 8 Behavior of Flexural Members At Elevated Temperature Chapter 9 Behavior of Compressive Member At Elevated Temperatures Chapter 10 Behavior of Statically Indeterminate Structures At Elevated Temperatures Part 4 Theoretical Analysis and Practical Calculation Method Chapter 11 General Mechanical Characteristics of Inhomogeneous Section Chapter 12 Finite Element Analysis of Loading History for Structures Chapter 13 Practical Calculation Methods for Ultimate Strength of Member and Structure at Elevated Temperature Chapter 14 Fire Resistance Analysis and Damage Grade Evaluation of Structure.
Keywords: Reinforced concrete -- Effect of high temperatures on.; Reinforced concrete -- Testing.; Reinforced concrete -- Thermal properties.; elektronické knihy; electronic books